2023
DOI: 10.3389/fnana.2023.1076095
|View full text |Cite
|
Sign up to set email alerts
|

The ventrolateral prefrontal cortex is part of the modular working memory system: A functional neuroanatomical perspective

Abstract: For many years, the functional role of the ventrolateral Pre-Frontal Cortex (PFC) was associated with executive functions, specifically in the context of non-affective cognitive processes. However, recent research has suggested that the ventrolateral PFC is also involved in the attention system. The Ben Shalom model of the functional organization of the prefrontal cortex (2019) posits that the ventrolateral PFC selects perceptual stimuli after integration by the adjacent ventromedial PFC. This article reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Neuroimaging studies have revealed common brain regions, like the prefrontal cortex (PFC) and anterior cingulate cortex (ACC), activated during tasks involving working memory and attentional flexibility [76,77]. However, distinctions have also been found, with areas such as the ventrolateral prefrontal cortex being differently engaged in working memory and attention systems [78]. The phonological loop and visuo-spatial sketchpad, responsible for verbal and visuo-spatial working memory, respectively, also suggest neural differentiation [79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have revealed common brain regions, like the prefrontal cortex (PFC) and anterior cingulate cortex (ACC), activated during tasks involving working memory and attentional flexibility [76,77]. However, distinctions have also been found, with areas such as the ventrolateral prefrontal cortex being differently engaged in working memory and attention systems [78]. The phonological loop and visuo-spatial sketchpad, responsible for verbal and visuo-spatial working memory, respectively, also suggest neural differentiation [79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…There was a similar decrease in functional connectivity in the orbitofrontal cortex in people with Huntington's disease [20] responsible for processing somatosensory input and coupling sensory and motor signals to generate subsequent movements [29]. The ventrolateral prefrontal cortex is associated with executive functions, such as maintaining attention [30]. The orbitofrontal cortex controls stimulus-reinforcement association learning, and the inferior frontal gyrus is associated with language processing and production but has also been implicated in reductions in impulse control and a lack of risk aversion [31,32,33].…”
Section: Suicidalitymentioning
confidence: 95%
“…However, only little is known about the involvement of IFG in free choice tasks. The robust activation of this area is not unexpected given the established role of VLPFC in action control and executive functions (Segal & Elkana, 2023;Tops & Boksem, 2011). The VLPFC's executive role is debated, with suggestions of inhibitory control for cognitive and motor interference (Aron et al, 2014;Schaum et al, 2021), and working memory involvement (Segal & Elkana, 2023).…”
Section: Common Neural Substrates Across All Tasksmentioning
confidence: 99%